Comprehensive investigations on Life Cycle Climate Performance of unitary air-conditioners. (September 2021) - Wan, Hanlong; Cao, Tao; Hwang, Yunho; Radermacher, Reinhard; Chin, Simon
Highlight: LCCP is evaluated for unitary air conditioner with five different refrigerants. The major LCCP influencing factor is different by local emission factors. The LCCP of R-466A can be up to 8% lower than using R-410A. LCCP can be up to 8% different due to the Urban Heat Island effect. Abstract: Life Cycle Climate Performance (LCCP) evaluation of air conditioning systems helps to mitigate the carbon emissions from the rapidly expanding air conditioning systems. Nevertheless, different counties have different system evaluation standards, weather conditions, grid emission factors, and material carbon emission coefficients. Furthermore, new R-410A alternatives like R-466A were rarely discussed. Besides, some researchers used the weather station data instead of onsite weather data. However, the weather data collected from the UMDCP campus and the College Park airport in the USA were different up to 5 °C due to the heat island effect. This paper used a unitary air conditioner as a case study and compared the LCCP calculation results for 11 cities worldwide for five different refrigerants. As excellent candidates for replacing R-410A from the LCCP perspective, R-32, R-290, R-452B, and R-466A are considered in this study. Then, the results using field test data and weather station data were compared. In conclusion, annual energy consumption is a significant factor in high-emission-factor countries. In some low-emission-factor countries, the LCCP can be decreased by up to 60% by using R-290. The differences between the actual inlet air temperature to the outdoor unit and local weather station measured temperature can result in up to an 8% difference in LCCP. For future work, more works on futuristic assumptions for grid emission factors and variable speed systems are needed while considering the expansion of renewable energies and energy efficient variable speed systems.